Globalization and the German industrial production model - Gary Herrigel (Journal for Labour Market Research, 2015)
Globalization is transforming the German manufacturing production model. German manufacturing MNCs are shifting from servicing global demand via exports to a strategy of 'produce where you sell' FDI expansion in emerging global markets. This strategy is generating recursive dynamics that are transforming the demographic and role composition of German home country production locations. This, in turn, poses challenges for the German systems of industrial relations and for industrial policy that are only beginning to be addressed. Overall, the article's take home conceptual message is that contemporary manufacturing globalization processes are recursive: i.e.: actions taken outside of Germany, on all levels, have consequences for – and involve change in – organizations and practices within Germany.
Keywords: 330; Industrieproduktion; Globalisierung - Auswirkungen; multinationale Unternehmen; Industriebetrieb; Auslandsinvestitionen; Arbeitsbeziehungen; Industriepolitik; Organisationsstruktur; Automobilindustrie; Maschinenbau; Beschäftigungseffekte; Produktionsorganisation; outsourcing; Ausland; Niedriglohnland; Produktionsverlagerung